INFLUENT OF FINANCIAL CAPITAL ON ITS RENTABILITY AT COOPERATIVE OWN BY THE EMPLOYEE OF THE CITY OF SUKABUMI (KPRI-PKS) - Nani Pujiastuti (STIE Binaniaga, 2017)
The study is carried out to understand the problems on the financial capital, its rentability, and the influent of rentability on the financial capital at the Cooperative Own by the Employee of the City of Sukabumi (KPRI-PKS). The method used in this study is a descriptive associative. This methode is used to provide solution to the question on casual’s relation or influence of two variables. Correlation analysis technique, determination and regression is used. The data used in this study is the secondary data which was gathered from the financial report balance sheet and from the calculation net income (SHU) report. For collection of the data in this study is done through field research and literature survey. The study indicates, that the financial capital of KPRI-PKS from 2009-2013 is increased annually. The highest financial capital is reached in 2011 with total financial capital of IRD 757.982.120 and the lowest is in 2013 with the financial capital of IDR 368.134.591. The value of their capital rentability is fluctuated, but the trend is declining. The rentability value in 2009 could reach 15.70% and the lowest is in 2011 which is only 6.75%. It is clearly showed the during 2009 to 2011 the rentability is drop significantly due to the increase of financial capital percentage compare to the increase of SHU percentage. While between 2012 and 2013 rentability of the financial capital is smaller and the percentage of SHU increased. Based on this study, the financial capital do positively influence the rentability up to 61% and the rest of 39% is influenced by other factors which are not included in this study.Keywords : Financial capital, rentability.